2020
DOI: 10.1016/j.jpurol.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Consulting “Dr. YouTube”: an objective evaluation of hypospadias videos on a popular video-sharing website

Abstract: Introduction: Parents who make decisions about hypospadias repair for their child may seek information from online platforms such as YouTube. Objective:The purpose of this study was to evaluate the health literacy demand of hypospadias videos on YouTube using the Patient Education Materials Assessment Tool for Audiovisual Materials (PEMAT-A/V). Study Design:We performed a YouTube search using the term "hypospadias," limiting results to the first 100 videos. We excluded videos that were < 1 minute or > 20 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
1
20
1
1
Order By: Relevance
“…Our interclass correlation coefficient indicated good agreement among raters and was higher than a previously reported study of YouTube videos. 28 Our finding that only 20% of videos targeting Black men promoted shared decision making is significantly lower than a similar study looking at videos targeting all men, which found that about 50% promoted shared decision making. 23 Of note, fewer than half of the videos targeting Black men discuss prostate cancer disparities, which is currently recommended as a best practice by the USPSTF and is essential information for Black men deciding about screening.…”
Section: Discussioncontrasting
confidence: 83%
“…Our interclass correlation coefficient indicated good agreement among raters and was higher than a previously reported study of YouTube videos. 28 Our finding that only 20% of videos targeting Black men promoted shared decision making is significantly lower than a similar study looking at videos targeting all men, which found that about 50% promoted shared decision making. 23 Of note, fewer than half of the videos targeting Black men discuss prostate cancer disparities, which is currently recommended as a best practice by the USPSTF and is essential information for Black men deciding about screening.…”
Section: Discussioncontrasting
confidence: 83%
“…3,4 There are a number of academic studies about diverse branches of medicine and a few newly introduced studies about dentistry involving YouTube. [5][6][7][8] The investigations depend on determining reliability and quality of information in dentistry, using a range of appropriate discipline-specific search terms.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, video uploading is not subject to quality evaluation or preliminary review, thus validity of the data is a great concern 3,4 . There are a number of academic studies about diverse branches of medicine and a few newly introduced studies about dentistry involving YouTube 5‐8 . The investigations depend on determining reliability and quality of information in dentistry, using a range of appropriate discipline‐specific search terms.…”
Section: Introductionmentioning
confidence: 99%
“…These low scores indicate that the informative level of the RIRS videos available on YouTube was low and did not contain enough information. Similarly, studies evaluating videos related to other urologic diseases stated similar problems [ 13 15 ]. Given that all those who are reaching this information are not health care professionals, these results suggest that viewers can obtain misleading information.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies in the literature have evaluated video platforms for different urologic and nonurologic diseases [ 13 14 15 16 17 18 19 20 ]. To the best of our knowledge, however, videos for RIRS on YouTube have not been previously evaluated.…”
Section: Introductionmentioning
confidence: 99%